A composição verbal e visual em publicidades de revistas impressas na era da convergência - Ribeiro, Raquel Schmidt [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
In face of the digital revolution, new media have not replaced the old ones, and the emerging convergence paradigm integrates old and new media in very complex ways. The digital media came to offer possibilities of information, communication, fun and relationship in a different media environment. Traditional media, as well as traditional advertising - now coexist with digital media that, with mobile devices - tablets and Android phones - now provide the most interactive media that society has ever experienced. And the brands are increasingly joining in these technological supports. This reconfiguration in the perception and daily life of society, especially in the form of consuming and producing content, affected the way in which the brands maintain contact with their consumers; now, beyond traditional media, include in their communication strategy tactics, technologies and platforms to maintain ongoing contact with consumers. In this work, we verify how magazines are printed in this new media scenario with infinite possibilities of information, collaboration, appeal and contact. The study was initiated through a bibliographical survey through the revision of books, scientific articles, theses and monographs on the subject. Magazines of various editorial lines were selected and ads for analysis were selected in each issue of the journals. In the course of the work, we listed the possible elements present in the advertisements and we elaborated graphs that allowed us to understand which are the most recurrent elements in the publicity published in magazines currently printed. After the initial analysis, we sought to understand the visual and verbal composition of printed advertising, that is, the totality of the graphic elements that configure this advertising system, verifying its specificities in contemporaneity

Diante da revolução digital, as novas mídias não substituíram as antigas e o emergente paradigma de convergência integra novas e antigas mídias de formas cada vez mais complexas. Os meios de comunicação digital vieram para oferecer possibilidades de informação, comunicação, diversão e relacionamento num diferente ambiente de mídia. Os meios de comunicação tradicionais, assim como a publicidade tradicional -, agora convivem com a mídia digital que, com os dispositivos móveis - tabletes e celulares Android- disponibilizam atualmente os meios mais interativos que a sociedade já experimentou. E as marcas estão cada vez mais ingressando nesses suportes tecnológicos. Essa reconfiguração na percepção e cotidiano da sociedade, especialmente na forma de consumir e produzir conteúdo, afetou a forma como as marcas mantêm contato com seus consumidores; agora, além das mídias tradicionais, incluem, em sua estratégia de comunicação, táticas, tecnologias e plataformas para manter o contato contínuo com os consumidores. Nesse trabalho, verificamos como se compõem as publicidades impressas de revistas nesse novo cenário midiático com possibilidades infinitas de informação, colaboração, apelo e contato. O estudo foi iniciado através de um levantamento bibliográfico por meio da revisão de livros, artigos científicos, teses e monografias sobre o tema. Foram selecionadas revistas de linhas editoriais diversas e em cada exemplar das revistas foram selecionados anúncios para análise. No decorrer do trabalho, elencamos os possíveis elementos presentes nas publicidades e elaboramos gráficos que permitiram entender quais são os elementos mais recorrentes na publicidade veiculada em revistas impressas atualmente. Após a análise inicial, buscamos compreender a composição visual e verbal da publicidade impressa, ou seja, a totalidade dos elementos gráficos que... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Publicidade; Cartazes; Composição tipografica